MAQASID SYARIAH SEBAGAI INDIKATOR PEMBANGUAN SEBUAH PERGURUAN TINGGI ISLAMI (STUDI KASUS PADA UNIVERSITAS MUHAMMADIYAH MAGELANG) - Veni Soraya Dewi (Universitas Ahmad Dahlan, 2019)
Quality education is not only the responsibility of the government but also all elements of society. One of the determinants of the quality of education in Indonesia is the quality of university. Muhammadiyah as the largest socio-religious organization in Indonesia, is required to take part in social and political life at the local, national and global levels. In contrast to conventional organizations that only aim to maximize the wealth of the owner, Muhammadiyah's business charity in carrying out it must be based on the struggle to carry out business towards the realization of the true Islamic community. Based on this, the purpose of the Muhammadiyah's business charity should be derived from the life purpose of a Muslim with its implementation is mashlahah in the activities of Maqasid Sharia. Maqashid Sharia has five factors, namely maintaining religion, guarding the soul, maintaining reason, guarding offspring, and guarding property. These five things differentiate Islamic organizations from other national organizations. This study aims to determine the implementation of maqasid sharia factors as an indicator of Islamic University Development. The research method used in this study is qualitative research which is descriptive research and tends to use analysis. Qualitative research aims to explain phenomena in depth through deep data collection. Based on the Al Quran, Sharia Enterprise Theory and previous studies it can be concluded that Muhammadiyah Magelang University includes Islamic universities based on the Maqasid Sharia indicator.